Game Theory for Networks Third International ICST Conference, GameNets 2012, Vancouver, BC, Canada, May 24-26, 2012, Revised Selected Papers - Krishnamurthy, Vikram; Zhao, Qing.; Huang, Minyi; Wen, Yonggang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Game Theory for Networks (GameNets 2012) held in Vancouver, Canada, May 24-26, 2012. The 13 revised full papers were carefully selected from 24 submissions and are presented together with 7 invited papers. The papers focus on topics such as mechanism design, physical layer games, network mechanisms, stochastic and dynamic games, game-theoretic network models, cooperative games in networks, security games, spectrum sharing games, P2P and social networks and economics of network QoS.
Achievability of Efficient Satisfaction Equilibria in Self-Configuring Networks -- A Competitive Rate Allocation Game -- Convergence Dynamics of Graphical Congestion Games -- A Game Theoretic Optimization of the Multi-channel ALOHA Protocol -- Game-theoretic Robustness of Many-to-one Networks -- Marketing Games in Social Commerce -- Mean Field Stochastic Games with Discrete States and Mixed Players -- Network Formation Game for Interference Minimization Routing in Cognitive Radio Mesh Networks -- Noncooperative Games for Autonomous Consumer Load Balancing over Smart Grid -- Primary User Emulation Attack Game in Cognitive Radio Networks: Queuing Aware Dogfight in Spectrum -- A Stackelberg Game to Optimize the Distribution of Controls in Transportation Networks.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Artificial intelligence; Information Systems; Computer Science; Artificial Intelligence (incl. Robotics).; e-Commerce/e-business.; Computer Communication Networks; Information Storage and Retrieval; Management of Computing and Information Systems; Probability and Statistics in Computer Science